God's lunatics : lost souls, false prophets, martyred saints, murderous cults, demonic nuns, and other victims of man's eternal search for the divine /: lost souls, false prophets, martyred saints, murderous cults, demonic nuns, and other victims of man's eternal search for the divine. (©2010) - Unknown
No abstract available